Long term compressive testing of masonry - Test procedure and practical experience - Binda, L. (2008)
The sudden collapses in Italy (Civic Tower of Pavia 1989, Noto Cathedral, 1996) initiated the research into long term behaviour of historical masonry structures. Last decade, international ad hoc collaboration was established within several research institutes in Europe. The testing on masonry samples identified the creep behaviour as a possible cause of the collapse of historical masonry buildings. Secondly, research focused on the study of the factors affecting creep (rate of loading, stress level...) and efforts were made to set up the most suitable testing procedures to understand the phenomenon. The gained insight in the long term behaviour and its description by means of rheological models, is validated mainly by means of long term testing, identifying significant parameters (strain rate of secondary creep phase, damage parameters...). This contribution merges the ample experiences gathered over a period of more than 15 years and drafts a first guideline for a common description of the test setup, testing procedure, data-acquisition and -processing.